2016
DOI: 10.1186/s12931-016-0399-3
|View full text |Cite
|
Sign up to set email alerts
|

Weakly acidic pH reduces inflammatory cytokine expression in airway epithelial cells

Abstract: BackgroundAspiration lung disease (ALD) is a common cause of respiratory morbidity in children and adults with severe neurodisability (sND). Recent studies suggest that chronic microaspiration of gastric contents is associated with mild rather than low, airway acidification. We investigated inflammatory responses to infection by airway epithelial cells (AECs) exposed to weakly acidic media.MethodsUsing pH measurements from children with sND at high risk of ALD as a guide, we incubated AECs in weakly acidic (pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Furthermore, we assessed concentrations of vaginal microbiota metabolites reflective of those found in the vaginal lumen; cells present deeper within the vaginal epithelium may be exposed to different, and likely lower, concentrations of metabolites than those analyzed here. The effects of eubiotic metabolite mixtures were assessed here at pH 3.9, and although we did not find a significant immunomodulatory effect of pH 3.9 media alone on cervicovaginal cells in a previous study (Hearps et al, 2017), acidity has been shown to dampen inflammatory responses of other types of epithelial cells (Hackett et al, 2016). It therefore remains possible that low pH may be contributing to the antiinflammatory properties of the eubiotic metabolites shown here.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, we assessed concentrations of vaginal microbiota metabolites reflective of those found in the vaginal lumen; cells present deeper within the vaginal epithelium may be exposed to different, and likely lower, concentrations of metabolites than those analyzed here. The effects of eubiotic metabolite mixtures were assessed here at pH 3.9, and although we did not find a significant immunomodulatory effect of pH 3.9 media alone on cervicovaginal cells in a previous study (Hearps et al, 2017), acidity has been shown to dampen inflammatory responses of other types of epithelial cells (Hackett et al, 2016). It therefore remains possible that low pH may be contributing to the antiinflammatory properties of the eubiotic metabolites shown here.…”
Section: Discussionmentioning
confidence: 52%
“…Acidification of culture medium has been associated with diminished monocyte activity and TNFα secretion as a result of a decrease in the glycolytic flux in macrophages ( 51 ). Moreover, culture medium acidification results in reduction of IL-6 and IL-8 production from airway epithelial cells challenged with or without LPS ( 52 ). Overall this suggests a stimulus-dependent impact of acidification, which may contribute to the bioactivity of the Lr-CFS in HT-29 IECs challenged with IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…From a disease perspective, the microenvironment of some tumor types have been reported to be as low as pH 6.44 [58,59], and the ionic environment in the TME can dictate the fate of anti-tumor T cell immunity [60]. The impact of low pH on driving pathologic inflammation has been also been long appreciated [61][62][63]. The concept of immunoregulatory protein interactions being governed by the pH of the host tissue is a valuable one.…”
Section: Avenues For Unique Vista Targetingmentioning
confidence: 99%